Gênero textual fichamento de resumo: uma sequência didática para o ensino-aprendizagem nos semestres iniciais de cursos de graduação - BRITO, Ana Lúcia da Silva (Universidade Federal do Pará, 2020)
The current thesis is composed of action research, qualitatively and applied nature. It is about the production and application of a Didactic Sequence, intending at the development of writting skills of undergraduate students about the genre descriptive annotation, allowing them to write more adequately in specific contexts of communication such as academic, political, pedagogical or everyday. Deeming that Didatic Sequence is arranged around a discursive genre, the annotation descriptive is picked as genre to elaborate this work. To uphold this research, the theoretical assumptions of the discursive / textual genres were grounded on Bakhtin (2003) and Marcuschi (2005). With respect to the textual genre, Campos (2015), Rocha et al. (2017) and Weg (2006), and on the organization of SD, the postulates of Dolz, Noverraz & Schneuwly (2004) were sustained. Eleven initial productions and eleven final productions were assayed, the results of which evidenced the proficiency of the learners in producing the descriptive annotation. Thus, the research reveals that the Didactic Sequence, as a methodology, allows the gradual improvement in students' writing skills.